Malaria in Jayapura District, Papua Province, Indonesia and resistance to sulfadoxine-pyrimethamine (Medical Journal of Indonesia, 2007)
Malaria poses a major public health problem in Papua. The rapid spread of drug-resistant parasites and deterioration of the malaria control program following the monetary crisis and civil strife in the late 90'es have worsened the malaria situation in many areas of Papua. To re-assess the current magnitude of malaria problem, a malariometric survey was conducted in three sub-districts of Jayapura District, as well as antimalarial drug sensitivity test using sulfadoxine-pyrimethamine (SP) at the outpatient clinics of Abepura General Hospital (RSU), Hamadi Primary Health Center and Panti Asuhan Katolik Clinics, Sentani, Jayapura District, Papua Province. Screening of 543 subjects in three sub-districts revealed 185 malaria positive subjects, either with P. falciparum, P. vivax or mixed of the two species. All of the malaria cases were asymptomatic. In the SP drug sensitivity test, of the 56 subjects involved, 32 were classified as early treatment failure and two subjects were classified as late treatment failure. The remaining 22 subjects were classified as adequate clinical and parasitological response (ACPR). These results indicated that the surveyed area has a high malaria prevalence and treatment failure to SP and therefore alert to the need of deploying new antimalarial regiment that suit the remote setting. (Med J Indones 2007; 16:32-8) Keywords: malaria, sulfadoxine-pyrimethamine (SP) resistance, Jayapura District, Indonesia